Does surgical approach affect early outcomes following primary total hip replacement in obese patients?. Issue 3 (May 2021) - Zhang, John; Wyatt, Michael C; Frampton, Chris M; Anderson, Geoffrey
Aim: The aim of this study was to assess whether obese patients undergoing primary total hip replacement (THR) via a posterior approach had superior revision rates and Oxford Hip Scores (OHS) compared to those via a lateral approach. Patients and methods: This is a retrospective cohort study using prospective data from the New Zealand Joint Registry applying STROBE and RECORD guidelines. Patients undergoing THR since 2010 were stratified by body mass index (BMI) into obese (BMI 30–39 kg/m 2 ), and morbidly obese (BMI ⩾40 kg/m 2 ) groups. All-cause revision rates, and 6-month OHS post-surgery were compared between groups. Multivariate analysis was performed. Results: 12, 109 unilateral THRs in obese patients were identified. The mean follow-up was 2.8 years (range 0.01–6.95 years). Univariate analysis in the BMI ⩾ 40 group showed the posterior approach had a significantly lower all-cause revision rate (0.99/100 observed component years (ocys); 95% CI, 0.65–1.44/100 ocys) than the lateral approach (1.71/100 ocys (95% CI, 0.98–2.77/100 ocys), p  < 0.05). There was no significant difference in dislocation rates between the surgical approaches. OHS was statistically higher in the posterior approach group in BMI 30–39 patients ( p  < 0.001) but not clinically significant. Multivariate analysis showed femoral head size significantly influenced all-cause revision rates and mitigated against the increased risk associated with the surgical approach. Conclusion: The choice of surgical approach in obese patients conveys no advantage in overall revision rates in the short-term. Choosing an appropriate size of femoral head may be of greater importance than choice of surgical approach for obese patients in primary THR.